2016
DOI: 10.1007/s10689-016-9936-y
|View full text |Cite
|
Sign up to set email alerts
|

Cystic parathyroid glands in MEN1: A rare entity?

Abstract: Approximately 300 cases of sporadic parathyroid cyst (PCs) have been reported to date. Only two cases have been described in MEN1 so far. Detection by imaging could be challenging, especially in multiglandular primary hyperparathyroidism (HPT) and clinical outcome could be different. During the period 1990-2014, 71 MEN1 patients were operated for primary hyperparathyroidism in our centre. We report three cases of PCs in MEN1 patients affected by HPT, who underwent a total or subtotal parathyroidectomy with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous reports suggest that nonfunctional parathyroid cysts may arise from vestigial remnants of the third or fourth branchial cleft or coalescence of microcysts (17,18). For functional parathyroid cysts, a pre-existing parathyroid adenoma or carcinoma may cause cystic degeneration (16)(17)(18). In MEN1 cases, only five patients with parathyroid cysts have been previously reported (Table 3) (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports suggest that nonfunctional parathyroid cysts may arise from vestigial remnants of the third or fourth branchial cleft or coalescence of microcysts (17,18). For functional parathyroid cysts, a pre-existing parathyroid adenoma or carcinoma may cause cystic degeneration (16)(17)(18). In MEN1 cases, only five patients with parathyroid cysts have been previously reported (Table 3) (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology contributing to the development of parathyroid cysts remains unclear. Previous reports suggest that nonfunctional parathyroid cysts may arise from vestigial remnants of the third or fourth branchial cleft or coalescence of microcysts (17,18). For functional parathyroid cysts, a pre-existing parathyroid adenoma or carcinoma may cause cystic degeneration (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Our case provides practical evidence that MEN1 and thyroid tumors may coexist. MEN1 is a rare hereditary tumor syndrome inherited in an autosomal dominant manner and presents mostly as tumors of the parathyroid [15], endocrine pancreas (such as gastrinoma) [16] and anterior pituitary [17]. Other endocrine and nonendocrine lesions of MEN1, such as adrenal cortical tumors; carcinoids of the bronchi, gastrointestinal tract and thymus; lipomas; angio bromas; and collagenomas have been described [1,18].…”
Section: Discussionmentioning
confidence: 99%
“…Cavalli et al found that approximately 300 cases of sporadic parathyroid cyst (PCs) had been reported to 2017. Only two cases have been described in MEN1 [15]. Parathyroid cysts can be divided into functioning and nonfunctioning, and most parathyroid cysts are nonfunctioning.…”
Section: Discussionmentioning
confidence: 99%
“…They are rarely found in the posterior mediastinum, but if they are found in the posterior mediastinum they mostly originate from superior parathyroid glands. In addition, some rare clinical presentations or associations have been described, such as parathyroid cyst in systemic lupus [ 32 ] or in type 1 multiple endocrine neoplasia, a condition frequently leading to functional parathyroid adenoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%